DEVELOPING PROFICIENT READING SKILLS THROUGH STRATEGIC INSTRUCTION AND ACTIVE ENGAGEMENT - Kumush Kosimova Golib kizi (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract: Reading is not just a basic academic skill but a foundational element of lifelong learning and personal growth. Despite its significance, many underestimate the complexity of the reading process, assuming it to be an automatic or simple task. This article examines the cognitive and instructional dimensions of reading, with a focus on enhancing comprehension through effective strategies. Drawing on research and classroom-based practices, it outlines key approaches such as prediction, visualization, questioning, and inference to promote deeper textual engagement. The article also highlights the importance of early exposure to language and the role of teachers in developing critical reading habits.